Detection and molecular identification of infectious bronchitis virus isolated in Malaysia - Mohamed, Maizan (2000)
Infectious bronchitis is a disease of economic importance in the poultry industry in Malaysia. Currently, natural outbreaks of IB are controlled through the use of vaccine. However, outbreaks still occur in vaccinated flocks. One of the major factors speculated for these outbreaks is the heterologous protection afforded by the current standard IB vaccines against different IB virus (IBV) serotypes and variants present in the country. Rapid and sensitive methods for the detection and identification of serotypes causing these outbreaks would therefore be valuable to the understanding and control of IB. In this study, reverse-transcription polymerase chain reaction (RT-PCR) using the published primers (C2U/C3L, S1oligo3'/S1oligo5', S1oligo3'/S1Newoligo5', IBP1+IIBRP2-, IBVN2+IIBVN1- and UTR2+/UTR1-) were used to detect 14 Malaysian IBV isolates. Only primers UTR2+/uTR1- and IBP l +IIBRP2- were found to be able to detect all of the 14 Malaysian isolates. These primers could therefore be used as universal primers for the detection of Malaysian IBV isolates. The Sl gene of a Malaysian nephropathogenic IBV (MH5365/95) and the variable region in the S l gene of the remaining 13 IBV isolates were RT-PCR using primers Slolig05-1/Sl olig03' and TM897FffM1328R respectively. The PCR products were cloned, sequenced and compared the sequences with published sequences of the S1 gene of other IBV strains. Based on this sequence comparison, MH5365/95 was found to be different from the other IBV strains. The remaining 13 isolates were classified into 2 general groups. The first group, that was designated as Group A, consists of three isolates and was closely related (more than 95% homology) to Massachusetts type (M41), the most commonly used vaccine strain in this country. The second group which consists of 10 isolates was genetically different from the published IBVs showing not more than 82% homology with the published sequence. These 10 isolates were further subdivided into Groups B and C, comprising 7 and 3 isolates respectively. The 3 isolates of Group C belong to the same group as MH5365/95. The Group B isolates, however, were more closely related to the M41 serotype (about 82% in homology) compared with that of Group C isolates (less than 80%). There was about 78% nucleic acid homology when Groups B and C were compared. It could therefore be concluded that the outbreaks in this country were caused by the new strains of IBV, which were different from the vaccine strains, thereby resulting in the vaccines becoming less efficacious to protect the chickens against the local IBVs.